Imagine a Proposal to Ease Holy Quran Memorizing and Retaining based on Information Processing Theory (Surat Al Hadid as an Example) - Al- alawi, Elhamh Yahya Hussein; Aldaghaishi, Suaad Said Ali; Abo Rujilah, Abdulaziz Hadi Saleh (Journal of Educational and Psychological Sciences, 2020)
This study aims to design a new theoretical framework to help the Holy Quran memorizers not only to memories the verses but also to retain them. This design goes in accordance with the new perspective of data processing which points to the fact that profound data processing has a great impact on remembering the verses through three major ways: Keyword Method as a code for the word to be remembered, Colour as a way to recall information as evident by a number of research studies and Story Strategy as a way to enable recalling of verses by linking the words to be remembered with an innovative story with reference to the science of event; Surat Al Hadid as an example. In order to prove the effectiveness of this proposal, a descriptive analysis and semi experimental study was conducted on a sample of Holy Quran Circle students ‘Halaqah’. 80 male and female students were divided into four groups, two experimental groups and two controlled groups. The findings of the study have demonstrated positive effect of the proposed model in ease of memorizing verses of the Holy Quran. The results show that there is a significant difference between male and female in goodness of their hafiz for favor of male group.
Keywords: memorizing verses; memorizing aids; information processing; keyword; colors; story